Impact of social standing on sports injury prevention in a WHO safe community: intervention outcome by household employment contract and type of sport. Issue 7 (23rd June 2005) - Timpka, T; Lindqvist, K; Ekstrand, J; Karlsson, N
Abstract : Objectives: As physical activity is promoted as part of a healthy lifestyle, sports injuries are becoming an important public health concern in many countries. The objective of this study is to investigate rates of sports injuries before and after implementation of a WHO Safe Community program. Methods: Sports injury data were collected pre- and post-implementation from all individuals below 65 years of age during 1 year in the targeted municipality (population 41 000) and in a control municipality (population 26 000). A quasi-experimental design was used and individuals were divided into three categories based on household relationship to the labour market. Results: There were no differences between socio-economic categories regarding pre-intervention injury rates. No statistically significant post-intervention changes in injury rate were observed in the control area or among any females in either area. In the intervention area, a statistically significant (p = 0.011) decrease in injury rate was observed among male members of households in which the vocationally important member was employed. A statistically significant decrease was observed in injuries sustained in team sports among male members of households in which the vocationally important member was employed (p = 0.001) and among members of households in which the vocationally important member was self employed (p<0.05). Conclusions: The study indicates areas for improvement in the civic network based WHO Safe Community model. The results show that females, participants in individual sports, and members of non-vocationally active households were less affected by the interventions. These facts have to be addressed in planning future community based sports injury prevention programmes and their evaluations.